2005
DOI: 10.1080/10408690590957034
|View full text |Cite
|
Sign up to set email alerts
|

Lutein: A Valuable Ingredient of Fruit and Vegetables

Abstract: Lutein is a human serum carotenoid which is not synthesized by humans and thus must be obtained by the ingestion of food containing it such as fruits and vegetables. Lutein is present in different forms in those foods as all-trans-lutein, cis-lutein, epoxi-lutein, and lutein linked to proteins. It discusses if the intake of lutein or diets supplemented with lutein or diets rich in fruits and vegetables are important in the prevention of diseases like some cancers, cardiovascular diseases, etc., that may be aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 145 publications
4
81
0
5
Order By: Relevance
“…This was done by selecting the specific foods and beverages that both were consumed in the present study and had a high content of carotenoids. The selection of the carotenoid-rich foods was based on the carotenoid concentrations presented in the US Department of Agriculture's National Nutrient Database (24) and papers covering the applicable foods eaten in the present study (17,(25)(26)(27)(28)(29)(30) . Foods are presented in descending order from the most eaten for the following variables that were constructed.…”
Section: Construction Of the Carotenoid-rich Foods Variablesmentioning
confidence: 99%
“…This was done by selecting the specific foods and beverages that both were consumed in the present study and had a high content of carotenoids. The selection of the carotenoid-rich foods was based on the carotenoid concentrations presented in the US Department of Agriculture's National Nutrient Database (24) and papers covering the applicable foods eaten in the present study (17,(25)(26)(27)(28)(29)(30) . Foods are presented in descending order from the most eaten for the following variables that were constructed.…”
Section: Construction Of the Carotenoid-rich Foods Variablesmentioning
confidence: 99%
“…The main sources of lutein are vegetables and fruit. Calvo (2005) collected data of lutein concentration in 74 species of fruit and vegetables reported by 44 authors since 1990. He observed that lutein concentration in green vegetables (lettuce, broccoli, water cress, parsley, pea, spinach) was higher than in yellowish-white vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in many kinds of fruits and vegetables, especially in leafy vegetables. It is also found in yolk and eye tissues (Calvo, 2005;Čopíková et al 2005). Pure lutein is a red-orange crystallic substance soluble in fats and organic solvents, but insoluble in water.…”
Section: Luteinmentioning
confidence: 99%